Transcutaneous carbon dioxide monitoring during flexible bronchoscopy under sedation: A prospective observational study - Yaman, Ferda; Günal, Nesimi (Journal of Surgery and Medicine, 2020)
Aim: It is difficult to maintain the necessary depth of sedation during bronchoscopy, and hypoxemia, hypoventilation, and undesirable cardiovascular effects are often encountered. Transcutaneous carbon dioxide monitoring is a reliable means of detecting hypoventilation. The aim of this study was to determine the effects of transcutaneous carbon dioxide (tPCO₂) monitoring on the amount of propofol required for sedation and examine sedation-induced hypoventilation and other adverse events requiring intervention, such as stopping the procedure to ventilate during flexible bronchoscopy. Methods: This prospective observational study included 60 patients undergoing bronchoscopy who were administered propofol. Of these, 30 patients were observed with transcutaneous carbon dioxide, and 30 were observed without. Propofol was used for sedation in all patients and the amount of propofol was compared between the groups monitored and not monitored transcutaneously for carbon dioxide. The sedation level was determined with the subjective sedation scale of the group that was not monitored. Results: No significant differences were found between the groups in terms of propofol consumption or the number of patients who required airway interventions during the procedure (P>0.05 for both). In this observational study, the partial carbon dioxide pressure in arterial blood was measured with a transcutaneous carbon dioxide monitor, which is a non-invasive method, and the maximum carbon dioxide value measured in prolonged interventions was 85 mmHg. Hypoxia was not observed in patients who developed hypoventilation. Conclusions: Hypoventilation is inevitable during bronchoscopy. Transcutaneous carbon dioxide monitoring may be important for high-risk cardiovascular patients.